Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1056/nejmoa032089
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes at School Age after Postnatal Dexamethasone Therapy for Lung Disease of Prematurity

Abstract: Early postnatal dexamethasone therapy should not be recommended for the routine prevention or treatment of chronic lung disease, because it leads to substantial adverse effects on neuromotor and cognitive function at school age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
355
3
8

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 534 publications
(378 citation statements)
references
References 31 publications
12
355
3
8
Order By: Relevance
“…These benefits are undisputed, but there is growing concern over the use of repeated courses of GCs prenatally and their increasing use postnatally where the clinical benefits are poorly established (Finer et al, 2000; Yeh et al, 2004). The present data therefore provide substantial new evidence that exposure to synthetic GCs (0.075-0.15 mg/kg/day) at doses in the lower range or below those used in perinatal medicine (Jobe and Soll, 2004;Yeh et al, 2004;Kreider et al, 2006) can permanently disrupt the structural development and population size in DA pathways that are critical for normal behavioral, emotional, and cognitive processes. Although dexamethasone clearly lacks the mineralocorticoid receptor activity of cortisol/corticosterone released endogenously, the present findings raise the possibility that stress-induced elevations in maternal GCs (which are reflected in the fetal circulation (Gitau et al, 1998)) or activation of the fetal HPA axis (Gitau et al, 2001), could equally target the developing midbrain systems and contribute to behavioral disturbances and possibly the emergence of certain psychiatric conditions associated with disruption in these pathways, such as schizophrenia or ADHD.…”
Section: Gc Programming Of Midbrain Da Cytoarchitecturementioning
confidence: 67%
See 1 more Smart Citation
“…These benefits are undisputed, but there is growing concern over the use of repeated courses of GCs prenatally and their increasing use postnatally where the clinical benefits are poorly established (Finer et al, 2000; Yeh et al, 2004). The present data therefore provide substantial new evidence that exposure to synthetic GCs (0.075-0.15 mg/kg/day) at doses in the lower range or below those used in perinatal medicine (Jobe and Soll, 2004;Yeh et al, 2004;Kreider et al, 2006) can permanently disrupt the structural development and population size in DA pathways that are critical for normal behavioral, emotional, and cognitive processes. Although dexamethasone clearly lacks the mineralocorticoid receptor activity of cortisol/corticosterone released endogenously, the present findings raise the possibility that stress-induced elevations in maternal GCs (which are reflected in the fetal circulation (Gitau et al, 1998)) or activation of the fetal HPA axis (Gitau et al, 2001), could equally target the developing midbrain systems and contribute to behavioral disturbances and possibly the emergence of certain psychiatric conditions associated with disruption in these pathways, such as schizophrenia or ADHD.…”
Section: Gc Programming Of Midbrain Da Cytoarchitecturementioning
confidence: 67%
“…For example, in the rat, prenatal GC treatment and exposure to stress similarly alter adult expression of the GC receptors (GRs) in brain regions that are important in regulating negative feedback within the HPA axis, resulting in permanent changes in circulating corticosterone levels (Barbazanges et al, 1996;Weinstock, 2001;Owen et al, 2005). It is also increasingly evident that early exposure to GCs, as well as stressors, has marked effects on animal and human affective and neuromotor behaviors and cognition (Yeh et al, 2004;Owen et al, 2005;Van den Bergh et al, 2005). However, there is little direct evidence to relate the consequences of perinatal GC exposure to enduring changes in specific, phenotypically identified, central neurotransmitter populations.…”
Section: Introductionmentioning
confidence: 99%
“…Our results thus match closely the suppression of the enzymes responsible for acetylcholine biosynthesis and promotion of those responsible for catecholamine biosynthesis, and for the enhanced expression of adrenergic receptors noted previously for glucocorticoid effects on developing neurons in vivo and in vitro (Berse and Blusztajn, 1997;Black, 1978;Hu et al, 1996;Kreider et al, 2005aKreider et al, , 2006. Again, these are likely to contribute to the long-term alterations in cholinergic synaptic proteins, synaptic activity and related behaviors seen in animal models of perinatal DEX administration (Kreider et al, 2005a(Kreider et al, , b, 2006 and cognitive dysfunction in humans (Yeh et al, 2004).…”
Section: Discussionmentioning
confidence: 89%
“…Currently, 10% of all infants delivered in the US receive glucocorticoids, although only a small proportion are likely to have developed respiratory distress, so that hundreds of thousands of infants are treated unnecessarily (Matthews et al, 2002). Growing evidence indicates long-term liabilities from such treatment, including altered brain architecture (Murphy et al, 2001), and subsequent cognitive deficiencies (Doyle et al, 2000;Seckl, 2001;Yeh et al, 2004). Accordingly, recent reviews point out the drawbacks of the blanket use of glucocorticoids (Blackmon et al, 2002;Coe and Lubach, 2005;Newnham, 2001;Raff, 2004;Seckl, 2004), but nevertheless, the major comorbidities associated with preterm delivery make it difficult to assign a clear cause-and-effect relationship.…”
Section: Introductionmentioning
confidence: 99%
“…They were used to aid in decreasing infant dependence on ventilators and on oxygen (Halliday & Ehrenkranz, 2001a, 2001b. At school-age follow-up, preterm infants whose chronic lung disease was treated with long-term steroid tapering doses were identified to have poor neurodevelopmental outcomes (Yeh et al, 2004).Earlier studies with animals found a variety of alterations in neurobehavioral outcome following PNS exposure (Benesova & Pavlik, 1989;Meaney & Stewart, 1981;Weichsel, 1977). Studies on sheep found that greater exposure to early steroid decreased fetal growth (Jobe, Wadda, Berry, Ikegami, & Ervin 1998).…”
mentioning
confidence: 99%